Modelling and Analysis of Real Time Power System With Cascaded Multilevel STATCOM Using Fuzzy Controller (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Electric Power is a major concern that has generated more importance in electrical utilities and consumers. To assure a reliable and quality power system, all the bus are expected to maintain steady acceptable voltage before and after being subjected to any disturbance. Among the FACTs devices a static synchronous compensator(STATCOM) is analyzed to provide a reliable and feasible solution. The STATCOM has been developed using cascaded multilevel converter.Â  A FUZZY based controller for Cascaded Multilevel STATCOM is developed which produces improved performance.This paper presents a comprehensive analysis of CMC based STATCOMÂ  with fuzzy controller in real time power system concerning the problem of variable loading and losses. A real time substation with 20 bus are analyzed with power flow analysis with and without STATCOM. Without the connection of STATCOM, a observable changes in the system voltage, line flows and losses are in system behaviour. But this influences the quality of grid and hence the customers are affected badly, indicating the need of power flow analysis and location of STATCOM on the system to improve the voltage profile. It is demonstrated that the described model works to an excellent level in improving the substation performance.